„Sud nad iskusstvom“ oder Wie im Gerichtsprozess gegen die Ausstellung Verbotene Kunst 2006 aus einem juristischen Prozess ein moralischer wurde - Sandra Frimmel (Slavica TerGestina, 2011)
In my text “‘Sud nad iskusstvom’ or How the court case against the exhibition Forbidden Art 2006 turned from a legal action into a moral one” I am analyzing certain strategies of the prosecution counsel, which made this legal action appear as a theater play. The curator of the exhibition Andrei Erofeev and the director of the exhibition venue, the Andrei Sakharov Center in Moscow, Juri Samodurov were sued by different representatives of orthodox organizations and charged with incitement to religious and national hatred under Art. 282, Par. 2b. In 2010 they were found guilty. The court case itself at various points very much resembled a theater play put on stage – starting with a “casting” of the witnesses through the Internet, cheat sheets for the witnesses with the text of their testimonies in the courtroom and coming to an end with comments and applause from the audience for their performances. Due to its resemblance to a play in the courtroom the trial of Erofeev and Samodurov is highly reminiscent of the Soviet show trials, which were consciously based on theatrical features such as a more or less set script. One can cite numerous interferences in the court case against Forbidden Art 2006 and the soviet show trials in terms of their theatrical (not political) features, among them letter and media campaigns generating a specific rhetoric serving the aim to characterize the “inner enemy” of the state. But in terms of the legal action against the organizers of the exhibition Forbidden Art 2006 , it was not only individuals who were charged for the purpose of identifying an inner enemy, as was the case in the Soviet show trials, but contemporary art as a whole. Herein lies a significant parallel between today’s trial and the predecessors of the show trials – the mock trials. The mock trials of early Soviet times were theatrical plays with amateur actors and dramatized legal proceedings to be taken as actual legal precedents. Until the early 1930s the fictional courtroom of the mock trial concerned itself with the creation and maintenance of new socialist morality. Therefore mock trials were not legal cases but moral cases. As they served the creation of new Soviet moral norms, the trial against Forbidden Art 2006 served the creation of new (traditionalistic and orthodox) artistic norms. The trial of Erofeev and Samodurov (and also other trials of artists and curators in today’s Russia in general) is therefore a moral case against contemporary art as a single social and cultural phenomenon, which deals irreverently with popular religious and national symbols in a way radically opposed to a traditionalistic approach to these symbols. One gets the impression that the orthodox society claims not only the exclusive right to interpret and utilize these symbols but also the power to decide what is acceptable art and what is not. This trial was designed to make an example to manifest aesthetic categories of art production as contemplated under the law.